Development of cork oak (Quercus suber L.) seedlings in response to tree shelters and mulching in northwestern Tunisia - Mechergui, Taher; Pardos, Marta; Boussaidi, Naceur; Hasnaoui, Brahim; Jacobs, DouglassF. (Journal of Forestry Research, 2013)
The need for reforestation in cork oak (Quercus suber L.) areas is challenged by difficulties. Principal among these is herbivory of young plants, vegetative competition, and slow growth rates of cork oak seedlings. We evaluated the early development of cork oak seedlings treated using tree shelters and mulching in northwestern Tunisia. We tested three tree shelter treatments (non-vented, vented, and control) to shield seedlings from animal damage and five mulch types to control competing vegetation (Italian Stone Pine, Lentisk, combination of Italian Stone Pine and Lentisk (organic mulches), gravel (inorganic mulch) and no mulch). At the end of the two-year experiment, sheltered seedlings were 89-99% taller than unsheltered seedlings and had higher numbers and lengths of shoot growth flushes. In contrast, both stem diameter growth and dry weight biomass (from samples extracted after two years) were significantly reduced inside tree shelters. Root-to-shoot ratio was not significantly different in sheltered vs. unsheltered seedlings, suggesting that tree shelters do not adversely affect this parameter. Mulching alone did not favour growth, but could be beneficial when combined with tree shelters. The combination of vented tree shelters and gravel mulch was the most effective treatment for promoting diameter, height and stem volume growth.
Keywords: Afforestation; mulching; polycyclism; Quercus suber L.; seedling growth; tree shelter

Development of Quercus ilex plantations is related to soil phosphorus availability on shallow calcareous soils - Pascual, S; Olarieta, J R; Rodríguez-Ochoa, R (New Forests, 2012)
The objective of this study is to analyse the performance of Quercus ilex plantations established under semiarid conditions on different soils formed on calcareous and gypsiferous parent material. We studied eighteen 300 m 2 plots in which 1 year-old seedlings had been planted after subsoiling on the contour. Plots were stratiﬁed according to aspect (north and south) and previous land use/parent material: shrubland on limestone (LM-SH), shrubland on gypsum rock (GY-SH), and cropland on colluvium (CO-AG). Soils developed on limestone and colluvium had average rooting depths of 27 and 37 cm, respectively, and mean concentrations of active lime and phosphorus (P) of 130 and 190 mg g -1 and 10 and 19 mg kg -1 , respectively. Soils developed on gypsum had a mean rooting depth of 26 cm, and a mean gypsum concentration of 73 %. Height and diameter of trees varied signiﬁcantly according to parent material/previous land use but not to slope aspect. Mean height and diameter of trees were signiﬁcantly higher in CO-AG plots than in LM-SH and GY-SH plots. Soil P and depth were the main variables explaining differences in dominant height across all 18 plots. In CO-AG plots mean height was negatively related to soil pH but positively related to soil P concentration. In LM-SH plots, mean diameter and height were negatively related to active lime concentration. This study suggests that soil P is a major determinant of holm oak performance in shallow calcareous soils and highlights the importance of conducting detailed soil studies in order to assess the viability of plantations with this species.
Keywords: Active lime; Afforestation; Gypsum; Holm oak; Mediterranean; Semiarid areas

Soil Gypsum and Increased Penetration Resistance Restrict Early Growth of Quercus ilex Plantations - Olarieta, J. R.; Rodríguez-Ochoa, R.; Ascaso, E. (Arid Land Research and Management, 2012)
The objective of this study is to analyze the influence of soil characteristics on the early growth of Quercus ilex in order to support planning of future plantations. We studied 31 200-m2-plots on 10-year-old plantations in fields that were set-aside from agriculture in a semiarid area in northeast Spain. Tree height and diameter, slope, geomorphic position, and various soil characteristics were measured. On north-facing slopes height and diameter of trees were significantly greater (150?200%) in soils without gypsum than in soils with gypsum. In soils without gypsum, increased penetration resistance in the upper 50 cm of soil (from 4.4 MPa to more than 7.0 MPa) decreased dominant height of trees to 40% of the maximum. While plantations of Quercus ilex can achieve satisfactory growth in semiarid conditions, detailed field studies of soil and site conditions are required for successful plantation establishment. The actual need for soil preparation treatments should be carefully evaluated considering species response and soil penetration resistance.
doi: 10.1080/15324982.2012.680654doi: 10.1080/15324982.2012.680654The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Afforestation; calcareous soils; land evaluation; soil rootable depth

Historical review of land use changes in Portugal (before and after EU integration in 1986) and their implications for land degradation and conservation, with a focus on Centro and Alentejo regions - Jones, Nádia; de Graaff, Jan; Rodrigo, Isabel; Duarte, Filomena (Applied Geography, 2011)
Changes in land use and production systems are to a large extent responsible for land degradation. In Portugal this process has been triggered mainly by socioeconomic drivers, such as agricultural technology, demography and policy changes. In this article land use changes in Portugal are discussed in terms of their main drivers and impacts, focussing on land degradation and conservation. The discussion includes a brief outline of historical land use changes in Portugal and a more detailed account of the changes in the period after 1986, when Portugal joined the European Union. An assessment of recent (1986e2006) land use changes and their impact was conducted for two selected research areas in the Centro and Alentejo regions. This assessment was based on information from the CORINE Land Cover programme (1985 and 2006) and the National Agricultural Census (1989 and 1999). In the Centro research area the land under forest declined from 52% to only 22% of the area, mainly as a result of forest ﬁres. In the Alentejo research area the major change was the decline of miscellaneous shrub, declining from 23% to 11%, to open forest land, increasing as a result of afforestation measures from 1% to 22%. These land use changes resulted in a signiﬁcant increase of soil loss estimates through RUSLE. In the Centro research area soil losses greater than 10 t ha 1 yr 1 were estimated to occur in 57% of the area in 1990, increasing as a result of land use change to 64% in 2006. In the Alentejo research area this change was from 65% in 1990 to 72% in 2006. The research raises questions regarding land use management, in relation to the Common Agriculture Policy support during the 1986e2006 period. Despite the increase in forest and permanent grassland areas, soil loss rates remain very high in the two research areas.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Afforestation; Agri-environmental policy; History; Land degradation; Land-use changes; Portugal

Afforestation improves soil fertility in south-eastern Spain - Serrano, L Rojo; Jime, M N; Ferna, E; Ferna, J; Roca, A; Aguilar, J; Fernandez-Ondono, E; Rojo Serrano, L; Jiménez, M N; Navarro, F B; Diez, M; Martin, F; et al. (EUROPEAN JOURNAL OF FOREST RESEARCH, 2010)
In the 20th century, in the Mediterranean area, many extensive afforestation efforts were made with the primary objective of protecting soils from erosion and improving their fertility. This study evaluates the effects of the afforestation undertaken in the Guadalentin basin (SE Spain) with respect to the organic and inorganic soil constituents and physico-chemical soil properties. Given the phytoclimatic environments in the basin (sclerophyllous and hyperxerophyllous), paired samples were taken beneath the tree canopy of the pine plantations and in nearby open zones. With the same methodology, samples were taken from areas considered to be native forest. The data were submitted to different multivariate analyses of variance (two-way MANOVAs) in order to compare the effects and interactions of the factors CANOPY (with and without trees), PHYTOCLIMATE (sclerophyllous and hyperxerophyllous), and TYPE OF FOREST (afforested or native) on the dependent variables measured (soil variables). Significant differences were found at 0-10 cm in soil depth under pine afforestations in relation to adjacent open areas. Below this depth, differences were found only between phytoclimatic environments. No significant interactions were found between the variables analysed at any of the depths, indicating that the effects of the afforestations on the soil characteristics were independent of the phytoclimatic environment. The afforestation in the Guadalentin basin, in the two phytoclimatic environments considered increased the soil fertility. Nevertheless, the native forests presented the highest soil organic-carbon contents, mainly in the sclerophyllous phytoclimate type (Quercus ilex subsp. ballota forests). Therefore, although the afforestations improved the soil fertility in relation to the open areas, the maximum potential has probably not been reached in relation to that observed in the native forests. The effects that forest development (age, basal area) over time exerts on soil properties remain to be verified by further research.
Keywords: Afforestation; Differential pedological characteristics; Guadalentin basin; organic carbon

Retention of native vegetation within the plantation matrix improves its conservation value for a generalist woodpecker - Barrientos, Rafael (Forest Ecology and Management, 2010)
The suitability of plantation monocultures for the conservation of forest animals is an issue under continous debate. The adaptability of forest dwellers and the forest management regime seem to play key roles. In this study, I investigated the habitat selection of a generalist bird, the great spotted woodpecker (Dendrocopos major), within a pine (Pine spp.) monoculture, as well as the importance of the native habitat features within the pine matrix for the species’ conservation. I compared 52 plots with woodpecker presence against 121 plots where the species was absent, as well as 68 nest-trees against 90 random ones. Regression analyses were used to investigate the habitat attributes involved in the habitat selection. Although the great spotted woodpecker is considered a generalist forest dweller, it shows a marked habitat selection. Based on presence/absence records, the woodpecker prefers wellforested patches with high levels of tree diversity and with good coverage of a secondary species such as the strawberry tree (Arbutus unedo). To excavate their nests, woodpeckers select large trees in patches where other trees are also larger, rejecting patches with a high number of small trees. The most striking conclusion from this work is the preference shown for native trees, especially Portuguese oaks (Quercus faginea), as nest-trees. This is noteworthy because native trees are smaller and they are surrounded by smaller trees than pines. These ﬁndings support that woodpecker conservation beneﬁts from an increase of habitat heterogeneity, particularly by the retention of native woodland patches within the plantation matrix.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Afforestation; Biodiversity conservation; Forest management; Forest policy; landscape ecology; Plantation design

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid

Performance di recenti imboschimenti con quercia da sughero in ex-coltivi - Dettori, S; Falqui, A; Filigheddu, M R; Sedda, L (iForest - Biogeosciences and Forestry, 2006)
Recently, significant forestry activities have taken place in Sardinia thanks to EU Regulation 2080/92 funds. Some 80% of the afforestated surface has been planted with holm oak and cork oak. The latter also characterizes 89% of the reforestation area. Given the funding source, plantations have been established on farmlands. Growth performances of these recent cork oak stands have been quantitatively evaluated and compared with the performances of two experimental plots. In Gallura (north-east of Sardinia), that is the traditional cork production area and still is economically the most important cork district of the island, these new cork oak plantations have an average size of 28 ha. They have been established on lands that, before plantation, were either pastures (30%) or arable lands (70%). Plantation failures are limited to 8.8% of the total (in term of mass) and seem independent of environmental factors or plantations species composition (conifers have been frequently used as secondary species). Average growth of the stem, measured above cork at collar height, is in the range 4 to 8mm/year with a mean value of 5.5mm/year. No correlation appears with either environmental conditions or species composition of the plantations. In the first experimental plot, soil management practices (natural vegetation removal vs its cutting and mulching) does not differentiate young plants growth trends. In the control subplots (no removal) stem collar diameter is 20% smaller. Localized manual hoeing around trunk base increased the diameters by 13% but reduced cork thickness by 21%. The second experimental plot allows comparisons among 27 Mediterranean proveniences of cork oak. The trial exhibits reduced genetic influence: diameters and heights growth are significantly different only among extreme groups. In conclusion, reduced growth performances of the plantations established in farmlands is due, to some extent, to the limitations inherent with private land management (constrained to costs minimization) and, on the other hand, to the generally very limited thickness of Gallura soils. Demand for good quality commercial cork is steadily raising. To sustain the request, in the short term, it would be necessary to extend financial support for plantations care, from 5 to 10 years, or even up to the first stripping (virgin cork).
Keywords: Afforestation; Cork oak; Growth; Performance; Reg EEC 2080/92; Sardinia

Performance di recenti imboschimenti con quercia da sughero in ex-coltivi - Dettori, S.; Falqui, A.; Filigheddu, M. R.; Sedda, L. (iForest - Biogeosciences and Forestry, 2006)
Recently, significant forestry activities have taken place in Sardinia thanks to EU Regulation 2080/92 funds. Some 80% of the afforestated surface has been planted with holm oak and cork oak. The latter also characterizes 89% of the reforestation area. Given the funding source, plantations have been established on farmlands. Growth performances of these recent cork oak stands have been quantitatively evaluated and compared with the performances of two experimental plots. In Gallura (north-east of Sardinia), that is the traditional cork production area and still is economically the most important cork district of the island, these new cork oak plantations have an average size of 28 ha. They have been established on lands that, before plantation, were either pastures (30%) or arable lands (70%). Plantation failures are limited to 8.8% of the total (in term of mass) and seem independent of environmental factors or plantations species composition (conifers have been frequently used as secondary species). Average growth of the stem, measured above cork at collar height, is in the range 4 to 8mm/year with a mean value of 5.5mm/year. No correlation appears with either environmental conditions or species composition of the plantations. In the first experimental plot, soil management practices (natural vegetation removal vs its cutting and mulching) does not differentiate young plants growth trends. In the control subplots (no removal) stem collar diameter is 20% smaller. Localized manual hoeing around trunk base increased the diameters by 13% but reduced cork thickness by 21%. The second experimental plot allows comparisons among 27 Mediterranean proveniences of cork oak. The trial exhibits reduced genetic influence: diameters and heights growth are significantly different only among extreme groups. In conclusion, reduced growth performances of the plantations established in farmlands is due, to some extent, to the limitations inherent with private land management (constrained to costs minimization) and, on the other hand, to the generally very limited thickness of Gallura soils. Demand for good quality commercial cork is steadily raising. To sustain the request, in the short term, it would be necessary to extend financial support for plantations care, from 5 to 10 years, or even up to the first stripping (virgin cork).
The following values have no corresponding Zotero field: pub-location: Dipartimento di Economia e Sistemi arborei Universit di Sassari, via E. De Nicola 9, 07100 Sassari. publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Afforestation; Cork oak; Growth; Performance; Reg EEC 2080/92; Sardinia

The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
The following values have no corresponding Zotero field: accession-num: 16762400
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - VILLAR-SALVADOR, P; Planelles, R; Enrı́quez, E; Rubira, J.Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. - Vázquez, F M; Suárez, M A; TORRES, E; CUEVAS, S (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize
Keywords: Afforestation; coccifera; Extremadura; faginea; Quercus; rotundifolia; suber; sylvicuIture

Supervivencia y crecimiento de encina ALCORNOQUE (Quercus suber) UTILIZANDO SEIS TIPOS DE TUBOS INVERNADERO - NAVARRO CERRILLO, R M; MARTÍNEZ SUÁREZ, A (II Congreso Forestal Español, 1997)
Achieving acceptable survival and growth of oak species on afforestation practices has been difficult. Several alternatives to improve establishment have been proposed, seeing that treesshelters are one of the most effective protection in improving survival and initial growth. Six kinds of treeshelters to improve establisment of Quercus ilex and Quercus suber were investigated
Keywords: Afforestation; Q.suber; Quercus ilex; Treeshelters